A preliminary study on wildlife roadkill incidents in Jeli, Kelantan (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Roadkill leads to biodiversity destruction, which cause threats to human well-being as harmful as climate change. Nowadays, people observe roadkill accidents as a natural occurrence, hence no proper record or study has been taken especially in a remote area. Therefore, this study was carried out to properly record the roadkill incidents at different road types and time. Data were collected in two different time ranges for three months. The morning session runs from 8-11 a.m. and the afternoon session runs from 4-7 p.m. Two types of roads were selected which are Jeli-Gerik highway and the local road in the Jeli area with a total distance of 30 km. Parameters recorded during the survey were types of dead animals found on the road, type of road, location and time. A total of 21 road-kill incident cases were registered, with mammals accounting for 33%, reptiles for 33% followed by birds (23%) and the remainder was from amphibian species. By systematically compiling and recording the numbers of road-kill incidents, a huge amount of data could be generated. Thus, it will take a whole new level of roadkill observation, especially in the Jeli area for the purposes of wildlife tracking and monitoring.
Keywords: Roadkill; Spotteron; Jeli; Wildlife; Collision